Analysis of Key Control Points of Microbial Contamination Risk in Pork Production Processes Using a Quantitative Exposure Assessment Model - Yang, Tengteng; Zhao, Ge; Liu, Yunzhe; Wang, Lin; Gao, Yubin; Zhao, Jianmei; Liu, Na; Huang, Xiumei; Zhang, Qingqing; Liu, Junhui; Zhang, Xiyue; Wang, Junwei; et al. (Frontiers in Microbiology, 2022)
Pork is one of the most common foods causing microbial foodborne diseases. Since pork directly enters the market after slaughtering, the control of microbial contamination in the slaughtering processes is the key to ensuring the quality and safety of pork. The contamination level of Escherichia coli, a health-indicator bacterium, can reflect the risk level of potential pathogens. In order to assess the E. coli exposure risk of pork during slaughtering and to identify the key control points, we established an E. coli quantitative exposure assessment model for swine-slaughtering processes in slaughterhouses of different sizes. The model simulation data indicated the E. coli contamination pattern on the surfaces of swine carcasses during slaughtering. The changes in E. coli contamination were analyzed according to the simulation data of each slaughtering process. It was found that the number of E. coli after trimming in big and small slaughterhouses increased to the maximum values for the whole processes, which were 3.63 and 3.52 log10 CFU/100 cm2, respectively. The risk contribution of each slaughtering process to the E. coli contamination on the surface of terminal swine carcasses can be determined by correlation analysis. Because the absolute value of correlation coefficient during the trimming process was maximum (0.49), it was regarded as the most important key control point. This result can be further proved via the multilocus sequence typing of E. coli. The dominant sequence type before trimming processes was ST10. ST1434 began to appear in the trimming process and then became the dominant sequence type in the trimming and pre-cooling processes. The model can provide a theoretical basis for microbial hygiene supervision and risk control in swine-slaughtering processes.